Coalizões no subsistema da política do acordo de Associação Mercosul-União Europeia - Grego, Letícia Bernardes de Mello (Universidade Federal de São Carlos, 2021)
The Mercosur - European Union Association Agreement was finalized in June 2019, after approximately 20 years of negotiation. The member countries and other actors had divergent interests and expressed their opposition or support to the agreement under various arguments, while protectionism of the agricultural sector of the European Union was the most prominent justification among the opponents. While some actors stand out for how they emphasized their position, it is unclear which coalitions are behind the forces that guided the negotiations and which actors took part in them. The Advocacy Coalition Framework (ACF) offers the theoretical basis for the study of coalitions, which is a way for individuals and organizations to join their resources and knowledge in order to imprint their preferences in public policies. This work had the objective of identifying the coalitions of the subsystem of the negotiations of the Mercosur-European Union Association Agreement between 2010 and 2019, by verifying the presence of the two minimum attributes of a coalition, according to Weible et al. (2019): the presence of actors who constantly tried to influence the outcome of the policy and shared policy-core beliefs. Process tracing was used to validate hypotheses formulated about which main state actors shared policy-core beliefs. A coalition between France, Ireland and Belgium was identified in advocacy of higher protectionism of the EU agricultural from 2010 to 2019. These same states formed a coalition that demanded stricter environmental protection policies from the signatories as a condition of the Agreement in 2019. Brazil, Spain and Uruguay formed a coalition in support of trade liberalization between the blocs, of which Paraguay has been a part since 2015.
Coalitions in the policy subsystem of the Mercosur-European Union Association Agreement
Keywords: Modelo de coalizões de defesa; Comércio exterior; Acordo de associação; Advocacy coalition framework; Foreign trade; Association agreement; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS::ANALISE INSTITUCIONAL